Environmental productivity index GIS‐based model to estimate prickly pear biomass potential availability for biogas production. (11th October 2022) - Leanza, Paola Maria; Valenti, Francesca; D'Urso, Provvidenza Rita; Arcidiacono, Claudia
Abstract: Nowadays, climate change is the environmental issue facing the world. To reach the 2030 European Union goals, recently, biogas production through anaerobic digestion has developed significantly, by using alternative biomass sources due to the competition between food and no‐food products. In this regard, Opuntia ficus‐indica ( OFI ) has been suggested as a suitable new biomass for producing biomethane within the context of circular economy. In this study, a predictive methodology was applied by combining the Nobel model of environmental productivity index (EPI) and geographic information system (GIS), with the aim of estimating OFI biomass amount, as well as biogas and electricity potential production. The GIS analyses allowed the identification of the most suitable territorial areas for producing biogas from OFI, and an estimation of electricity production. The achieved results are highly valuable information for strategic planning of biogas sector development and could be relevant to the intervention priorities established by the EU. Core Ideas: The use of Opuntia ficus indica biomass for anaerobic digestion was assessed. The methodology was applied by combining models and spatial analysis tools. The study was carried out from territorial data acquired at local scale. Based on bioclimatic data, the environmental productivity index was estimated. The most suitable areas for producing biogas and electricity per year and per hectare were computed.